Weir, Phyllis; Weir, Marguerite. Duplex house where the Weir's had their first shop. - Barrett, Terra (2014)
Duplex house on the Long Run where the Weir's had their first shop. Built by Marguerite Weir's grandfather John Roberts and his brother.